(untitled) (Gestão & Regionalidade, 2022)
The thematic addressed in this article is about organizational hybridism as a lens for understanding organizations that develop in multiple institutional logics, acting in markets governed by certification standards such as Fairtrade. Thus, the aim of this study is to analyze how Fairtrade certification mechanisms influence the organizational design of cooperatives as hybrid organizations. This investigation is structured from a qualitative research, of exploratory character, carried out from a case study in a cooperative of Fairtrade coffee growers of Espírito Santo, using the triangulation of data collection techniques through semi-structured interviews, non-participant observation and documents, analyzed from content analysis. The main results pointed out the need to forge the design of the cooperative to Fairtrade design to adapt to the normative instruments, creating specific governance mechanisms to avoid the loss of legitimacy.